Organic Nanostructures for Next Generation Devices - Al-Shamery, Katharina; Rubahn, Horst-Günter; Sitter, Helmut (Springer Series in Materials Science,, 2008)
This book provides the first comprehensive overview of fabrication, fundamental properties and applications of a new class of nanoscaled organic materials which holds huge promise for future submicron-sized photonics and optoelectronics. By controlled self-assembled growth on single crystal surfaces, fiber-like structures are fabricated with macroscopic lengths up to millimeter size but mesoscopic widths of mere hundreds of nanometers and nanoscopic heights of several ten nanometers. The extraordinary beauty of these new structures is that they are quasi single crystalline, providing superior optical and electronic properties, and that their properties can be freely tailored via functionalization of their organic building blocks.